2002
DOI: 10.1002/ajmg.10397
|View full text |Cite
|
Sign up to set email alerts
|

HOXD13 polyalanine tract expansion in classical synpolydactyly type Vordingborg

Abstract: In 1927, Oluf Thomsen, in a classic paper, described a seven-generation family with autosomal dominant axial synpolydactyly (SPD)--the Vordingborgtyp of axis duplication and dysostosis. Expansion of a polyalanine tract in the HOXD13 gene is known to cause synpolydactyly. We have rediscovered part of the family described by Thomsen, and detected a 9 triplet polyalanine expansion within HOXD13segregating with the disorder. The phenotypic spectrum in mutation carriers ranged from severe to inapparent bone malform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 6 publications
2
22
0
Order By: Relevance
“…Expansions of a polyalanine stretch in homeobox gene HOXD13 at 2q31 have been implicated in this type [Akarsu et al, 1996;Muragaki et al, 1996;Kjaer et al, 2002]. Studies have shown that type I syndactyly is also linked to the long arm of chromosome 2, in close vicinity of SPD locus at 2q34-q36 [Bosse et al, 2000] and that, there is genetic homogeneity in syndactyly type I [Ghadami et al, 2001].…”
Section: Discussionmentioning
confidence: 95%
“…Expansions of a polyalanine stretch in homeobox gene HOXD13 at 2q31 have been implicated in this type [Akarsu et al, 1996;Muragaki et al, 1996;Kjaer et al, 2002]. Studies have shown that type I syndactyly is also linked to the long arm of chromosome 2, in close vicinity of SPD locus at 2q34-q36 [Bosse et al, 2000] and that, there is genetic homogeneity in syndactyly type I [Ghadami et al, 2001].…”
Section: Discussionmentioning
confidence: 95%
“…5 Similar pathological polyalanine tract expansions in HOXD13 have subsequently been reported in other families with SPD. [6][7][8] Intragenic frameshift deletions in HOXD13, predicted to result in truncated proteins, and also an acceptor splice site mutation and a missense mutation in exon 2 of HOXD13, cause an atypical form of SPD. [9][10][11][12] Interestingly, a different missense mutation in the same exon has been found in a family with a dominantly inherited combination of brachydactyly and polydactyly.…”
mentioning
confidence: 99%
“…Sayli et al 10 showed that some family members may show polydactyly of the little finger and this was seen in one child of the first family. Several authors 5,11,12 showed that clinodactyly of the little finger may be a concurrent or isolated feature, indicating that the responsible gene may be expressed as an isolated clinodactyly and this was seen in the parents of the second family. Finally, Akarsu et al 1 and Muragaki et al 7 have described the 'homozygous' phenotype that is characterized by short hands, polygonal metacarpals/metatarsals, accessory carpal bones and tarsometatarsal fusion.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] It is characterized by bilateral synpolydactyly of the third web spaces of the hands and bilateral synpolydactyly of the fourth web spaces of the feet. It is inherited as autosomal dominant and the mutation has been localized to 2q31 (HOXD13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation